2023
DOI: 10.3390/polym15153213
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan (CS)/Hydroxyapatite (HA)/Tricalcium Phosphate (β-TCP)-Based Composites as a Potential Material for Pulp Tissue Regeneration

Abstract: This research focused on developing new materials for endodontic treatments to restore tissues affected by infectious or inflammatory processes. Three materials were studied, namely tricalcium phosphate β-hydroxyapatite (β-TCP), commercial and natural hydroxyapatite (HA), and chitosan (CS), in different proportions. The chemical characterization using infrared spectroscopy (FTIR) and X-ray diffraction (XRD) analysis confirmed the composition of the composite. Scanning electron microscopy (SEM) demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Embedding of β-TCP and HAp in the GB matrix has not changed the characteristic peaks. The characteristic peaks in both β-TCP and HAp were located at 970 and 1021 cm −1 , attributed to the stress vibrational modes of the (PO 4 ) 3− bond and vibration peaks at 600 and 540 cm −1 of the (PO 4 ) 3− [ 17 ]. The Amide I peak of GB corresponding to the vibration of the amide carbonyl group was shifted due to the cross-linking process from 1629 cm −1 to 1624 cm −1 , 1621 cm −1 , and 1619 cm −1 for GB-CA, GB-TCP-CA, and GB-TCP-HA-CA, respectively [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Embedding of β-TCP and HAp in the GB matrix has not changed the characteristic peaks. The characteristic peaks in both β-TCP and HAp were located at 970 and 1021 cm −1 , attributed to the stress vibrational modes of the (PO 4 ) 3− bond and vibration peaks at 600 and 540 cm −1 of the (PO 4 ) 3− [ 17 ]. The Amide I peak of GB corresponding to the vibration of the amide carbonyl group was shifted due to the cross-linking process from 1629 cm −1 to 1624 cm −1 , 1621 cm −1 , and 1619 cm −1 for GB-CA, GB-TCP-CA, and GB-TCP-HA-CA, respectively [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both hardness and E r for GB-TCP-HA-CA were lower than for GB-TCP-CA but still significantly higher than for GB. This reduction in comparison to GB-TCP-CA could be explained by the agglomeration of hybrid particles and the interaction between HAp and β-TCP [ 17 ]. Also, DSC analysis revealed that the lower T g for GB-TCP-HA-CA indicated that the cross-linking was affected by the presence of hybrid reinforcements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the organic-mineral interface in bones is predominantly polysaccharides [805], various biocomposites of CaPO 4 and polysaccharides, such as alginates [413,609,610,612,715,[806][807][808][809], as well as chitosan [426,450,468,490,519,556,[631][632][633][634][635][636][637][638][639][640][641][642][643][644]678,696,702,[810][811][812][813][814][815][816][817][818][819][820][821] and chitin [416,489,[822][823]…”
Section: Biocomposites With Other Bio-organic Compoundsmentioning
confidence: 99%